Writing Histories, Making Nations: A Review Essay - Marek Tamm (Storicamente, 2017)
Since the 1990s we have seen an increasing number of studies in the history of national history writing, in the ways in which peoples construct nations through the production of historiography. But a major breakthrough was made with a five-year ESF Scientific Programme “Representations of the Past: The Writing of National Histories in Europe (2003–2008), resulting in a eight-volume book series “Writing the Nation” published by Palgrave Macmillan in 2008–2015. This review essay delineates, first, the general architectonics of the series, to give an overview of its main results and findings. Then, secondly, some critical-methodological points are raised and some perspectives for future research suggested.